2004
DOI: 10.1002/esp.1111
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different methods of bed shear stress estimates in simple and complex flow fields

Abstract: Bed shear stress is a fundamental variable in river studies to link flow conditions to sediment transport. It is, however, difficult to estimate this variable accurately, particularly in complex flow fields. This study compares shear stress estimated from the log profile, drag, Reynolds and turbulent kinetic energy (TKE) approaches in a laboratory flume in a simple boundary layer, over plexiglas and over sand, and in a complex flow field around deflectors. Results show that in a simple boundary layer, the log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
207
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(254 citation statements)
references
References 38 publications
11
207
0
4
Order By: Relevance
“…TKE profiles peak at around 0Á1z/h (Figure 4), as has previously been observed for less rough-bed conditions (Nicholas, 2001;Biron et al, 2004). Above the maximum, TKE profiles closely follow the Reynolds stress profiles in their linear form.…”
Section: Tke Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…TKE profiles peak at around 0Á1z/h (Figure 4), as has previously been observed for less rough-bed conditions (Nicholas, 2001;Biron et al, 2004). Above the maximum, TKE profiles closely follow the Reynolds stress profiles in their linear form.…”
Section: Tke Methodssupporting
confidence: 81%
“…Nezu and Nakagawa (1993) suggested that the extrapolated Reynolds stress method gives the most reliable estimates. Biron et al (2004) and Rowinski et al (2005) used the Reynolds stress method as a reference to compare with results obtained by other methods. When results from other methods are plotted against those from the Reynolds stress method (Figure 8), no clear trend or tendency can be seen over the range investigated here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress (s, in g cm À1 s À2 ) is a common variable used to characterize sediment transport and deposition (Biron et al 2004). It is possible to estimate bed shear stress (s 0 ) from the Reynolds stress…”
Section: Methodsmentioning
confidence: 99%
“…Two common approaches to determine the friction velocity are (refer to detailed study by Biron et al [11]): (1) the measured Reynolds stress profile's extrapolation method; and (2) the energy gradient method. These approaches have been proven to reasonably calculate the friction velocity in different bed conditions [12,13], providing that the bed surface layer condition is relatively uniform through streamwise space.…”
Section: Friction Velocitymentioning
confidence: 99%